2017
DOI: 10.1038/srep46839
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Diabetes Onset at 31–45 Years of Age is Associated with an Increased Risk of Diabetic Retinopathy in Type 2 Diabetes

Abstract: Scientific Reports 6: Article number: 38113; published online: 29 November 2016; updated: 26 May 2017 The original version of this Article incorrectly included Haibing Chen as a corresponding author. This error has now been corrected in the PDF and HTML versions of this Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a pilot study conducted for the prevalence of DR in Pakistan, 3000 diabetic individuals were included with 26% of the patients having retinopathy; 52% of the patients were males and 48% females. 23 In a study conducted by Zou et al, 12 they included more than 5000 individuals, and the mean age of DR and non-DR was 58.2 ± 14.0 and 60.0 ± 12.0 years, respectively. Interestingly, Wubben 24 indicated that as a result of their research, retinal dysfunction, prior to the microvascular changes, could be detected with an elecroretinogram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study conducted for the prevalence of DR in Pakistan, 3000 diabetic individuals were included with 26% of the patients having retinopathy; 52% of the patients were males and 48% females. 23 In a study conducted by Zou et al, 12 they included more than 5000 individuals, and the mean age of DR and non-DR was 58.2 ± 14.0 and 60.0 ± 12.0 years, respectively. Interestingly, Wubben 24 indicated that as a result of their research, retinal dysfunction, prior to the microvascular changes, could be detected with an elecroretinogram.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound machine used in the study (Xerio, Toshiba) was equipped with a linear transducer that provided 7 to 14 MHz frequency, for the OA examination. 12 The research and examination techniques were explained to each of the patients. Each patient was placed in a recumbent position, with the head tilted back, or supine.…”
Section: Methodsmentioning
confidence: 99%